Greater left ventricular to right ventricular lead tip separation is associated with improved outcome after cardiac resynchronisation therapy. (22nd September 2015) - Ariga, R; Tayebjee, MH; Lefroy, DC
Abstract : Background: Approximately 30% of patients who undergo cardiac resynchronisation therapy (CRT) do not experience symptomatic benefit. In some cases, failure to respond may be due to suboptimal pacing lead positioning leading to inadequate resynchronisation. It has previously been shown that the pacing of lateral or posterior left ventricle segments is more likely to achieve a clinical response to CRT than pacing the anterior left ventricular wall. However, the limitations of transvenous lead placement may preclude access to the ideal left ventricular pacing site. It can be argued that depolarisation of the left ventricle will, in general, be completed more rapidly when the left ventricular and right ventricular pacing leads tips are widely separated than when they are close together. We hypothesised that left to right ventricular pacing lead tip separation is an important factor in determining optimal cardiac resynchronisation, and is a critical determinant of the clinical response to CRT. Methods: Eighty-six consecutive patients (mean age 71 ± 10 years, male (74%), coronary disease (71%), atrial fibrillation (23%), mean ejection fraction 29 ± 8%, mean QRS duration 160 ± 27 ms NYHA class III (81%) NYHA class IV (19%)) underwent CRT from January 2006 to September 2008. Median follow-up was 12 months and clinical response to CRT was defined as a reduction of NYHA class by one or more. The spatial separation between the right and left ventricular pacing lead tips was calculated using measurements obtained from orthogonal posteroanterior and lateral chest radiographs performed the day after implant. Results: 59 patients (69%) responded to CRT. There was a statistically significant association between increased lead separation and clinical response to CRT. Left to right ventricular lead tip separation was 103 ± 21 mm in the responder group versus 88 ± 25 mm in the non-responder group (mean ± SD, p = 0.009, Student's t-test). Conclusions: Greater separation between the left and right ventricular pacing lead tips is associated with an increased likelihood of clinical response to CRT. In achieving a response to CRT, obtaining a wide separation of left to right ventricular lead tips may be as important as obtaining a left ventricular lead tip position within a specific target left ventricle segment.